Towards a shared poetics of the Alexisphere. Natural Sciences as a metaphorical resource (Anclajes, 2026)
The Alexisphere is the artistic community that has formed over the past decade around Alexis Díaz-Pimienta, renowned repentist, researcher and writer, whose work in promoting the art of poetic improvisation in classical stanzas, particularly the décima espinela or ten-line stanza, is central. The Alexisphere brings together prominent poets and musicians alongside lesser-known authors of extraordinary potential on both sides of the Atlantic. The community shares a set of conventions, the first of which is the everyday use of the ten-line stanza, integrated into songs and poetry books, employed as a playful or convivial exercise, or used as a code of courtesy. Additionally, we can find certain recurring themes related to sciences, echoing Jorge Drexler’s lyrics and reflecting the background of some members of the Alexisphere in biology, medicine, or mathematics. This article examines specific cases of Alexispheric poets and musicians, including Javier Ruibal, Juan Luis Mora, Pedro Poitevin, Carlos Palacio “Pala”, José González and Bernard Engel, to trace the emerging contours of a shared poetics.
Keywords: Jorge Drexler; Alexisphere; Decima; Songs; Contemporary Poetry